Causes and forms of corruption in Nigeria : a case study of public officials - Ajiteru, Sherif Abdul Raheem (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study examines the perpetual causes and forms of corruption rooted in the socio-cultural, economic, and political practices of Nigeria. In Nigeria, corruption is regarded as notorious syndrome and contagious epidemic that has grossly affected Nigeria in its entirety. Many consider corruption the largest obstacle causing Nigeria's stagnation on every front and stifling economic growth by undermining her economic potential and development despite the nation's rich resources. The problem of corruption has reached such heights that Nigeria is often considered by many to be the very image of corruption. It devalues the quality of human life, deprives people of their alienable rights and basic quality of life. This dissertation aims at exploring the perceptions of public officials concerning the causes and forms of corruption in Nigeria. Doubtless, corruption impedes reforms thereby making Nigeria's reform policies ineffective. In sum, corruption practices in all strata in Nigeria can be attributed to high levels of poverty, high unemployment rates, low-remunerations, delays in the payment of wages by the government, over concentration of power, nepotism, tribalism, and dishonest leaders. There is a clear and urgent need for Nigeria to reverse the prevailing culture in which corruption is viewed as a permissible practice. Meanwhile, Nigerians should be educated and re-oriented on the malaise of corruption, and excessive wealth and culture of “get rich at all cost”. Data for this study are drawn from both primary and secondary sources in the form of books, reports, scholarly journals, magazines, and occasional papers, proceedings of relevant conferences, newspapers and internet sources. Questionnaires and interviews were conducted to complement the quantitative and qualitative methodology upon which this study is grounded. The research concludes by suggesting remedies among which are effective administrative reforms, hard-line punishment, e.g. death penalty, leaders with strong political will, inculcating religious cum cultural value and social ethics to assist the government in combating corruption in Nigeria. Likewise, civil service mechanisms such as transparency, legislative control, judicial, press and popular controls on officials should be streamlined as effective checks on corrupt practices.